Ovine small bowel “minute rhythm” intensity related to feeding and phase of migrating myoelectric complex - ROMAŃSKI, K. W. (Journal of the Hellenic Veterinary Medical Society, 2018)
The presented study was performed to characterize further the ‘minute rhythm’ in the ovine small bowel, notably to assess the role of fasting and feeding as well as of the phase of the MMC upon the number and amplitude of the MR-containing spike bursts. In eight rams the electrodes were attached to the pyloric antrum, duodenal bulb, duodenum and upper jejunum. In the course of chronic experiments, the myoelectrical recordings were conducted in fasted and non-fasted rams, before and after feeding offered during phase 2a or 2b of the MMC. The phases of the MMC and the MR episodes were identified and the MR frequency, the number of the spike bursts in one MR episode and their amplitudes were calculated. 74 per cent of the MR episodes exhibited the propagated character. At the beginning of phase 2a, the MR often arrived exclusively in the duodenal bulb and was disorganized, while at the end of phase 2b of the MMC, the MR-related spike bursts were most prominent and propulsive. In the duodenal bulb, the giant-like spike bursts forming the pattern were observed occasionally. The MR episodes contained usually 1-2 spike bursts. The number of the MR episodes, each containing one spike burst was smaller after feeding mostly in the duodenum and jejunum and it was lower during phase 2b than during phase 2a of the MMC in the duodenal bulb, duodenum and jejunum. The number of the spike bursts in one MR episode increased after feeding and during phase 2b of the migrating myoelectric complex and it was the highest in the jejunum. The spike burst amplitudes of the MR episodes were the highest in the duodenal bulb. Feeding during phase 2b of the MMC decreased the amplitude of the MR-related spike bursts both in the duodenum and the jejunum. It is concluded that the intensity of the MR in the ovine small bowel is related to feeding and to the phase of the MMC and the high variability of the pattern comprises its character and strength that are apparently related to the intraluminal influences affecting the controlling mechanisms.